Growth status of children and adolescents with type 1 diabetes mellitus - Khadilkar, Vaman V. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND AND OBJECTIVES: Growth parameters are important indicators of a child's overall health, and they are influenced by factors like blood glucose control in diabetic children. Data on growth parameters of Indian diabetic children is scarce. This retrospective, cross-sectional, case control study was conducted at diabetes clinic for children at a tertiary care center at Pune, to study growth parameters of diabetic children in comparison with age-gender matched healthy controls and evaluate effect of different insulin regimes and age at diagnosis of diabetes on growth. MATERIALS AND METHODS: One twenty five diabetic children (boys: 50) and age gender matched healthy controls were enrolled. All subjects underwent anthropometric measurements (standing height and weight). Mean height (HAZ), weight (WAZ) and body mass index (BAZ) for age Z scores were calculated. Diabetes control was evaluated by measuring glycosylated hemoglobin (HbA1C). Statistical analysis was done by SPSS version 12. RESULTS: Mean age of diabetic children and age gender matched controls was 9.7 ± 4.4 years. Diabetic children were shorter (128.3 ± 24.3 cm vs. 133.6 ± 24.7 cm) and lighter (29.2 kg ± 15.3 vs. 31.3 ± 15.4 kg). HAZ (−1.1 ± 1.2 vs. −0.2 ± 0.8) and WAZ (−1.2 ± 1.3 vs. −0.7 ± 1.3) were significantly lower in diabetic children (P < 0.05). Children on both insulin regimes (intensive and conventional) were shorter than controls (HAZ-intensive −1.0 ± 1.0, conventional −1.3 ± 1.3, control −0.2 ± 0.8, P < 0.05). HAZ of children who were diagnosed at <3 years of age was the least (−1.6 ± 1) amongst all diabetic children while those diagnosed after puberty (>14 years) were comparable to healthy controls. CONCLUSIONS: Growth was compromised in diabetic children in comparison to controls. Children diagnosed at younger age need more attention to optimize growth.